DEVELOPMENT OF STEAM-BASED E-LKPD TO IMPROVE CREATIVE THINKING SKILLS ON GEOMETRY TRANSFORMATION MATERIAL - Sridiasih, Imelda Nur Isnaini; Sabil, Husni; Junita, Ranisa (Prima: Jurnal Pendidikan Matematika, 2025)
Creative thinking in mathematics and other fields is an important life skill, especially in the era of information and increasingly fierce competition. The low ability of students' creative thinking is due to the learning process and learning methods that have not run optimally. STEAM learning emerged as an effort to overcome the shortcomings of previous learning methods. This research aims to improve creative thinking skills through the development of teaching media in the form of E-LKPD (Electronic Learners' Worksheet) based on STEAM (Science, Technology, Engineering, Arts, and Mathematics). The STEAM-based E-LKPD is designed using Liveworksheet. The method used in this research is the ADDIE method (Analysis, Design, Development, Implementation, Evaluation). The trial was conducted in one of the junior high schools in Jambi City by taking one of the ninth-grade classes at the school with a total of 28 students. Data analysis was measured using a Likert scale, and then the results of the creative thinking ability test were calculated using the N-Gain formula. The results showed that the STEAM-based E-LKPD met the product quality criteria, which included validity, practicality, and effectiveness. It was found that the percentage of material validity was 80% with “valid” criteria, and the design validity obtained a percentage of 91.4% with “very valid” criteria. For the results of the teacher's practicality, a percentage of 90.1% was obtained in the “very practical” category, and for the results of student practicality, a percentage of 82.0% was obtained in the “very practical” category. The effectiveness test obtained 87.8% with the category “very effective”. Then the N-Gain value obtained was 56.5%, which was in the “medium” category. So the STEAM-based E-LKPD teaching media is effective enough to improve creative thinking skills, so it is suitable for use in learning activities.